(untitled) (Sunari Penjor : Journal of Anthropology, 2025)
The Ministry of Agriculture (Kementan) gives encouragement to investors in sugar industry to increase the production capacity to meet the Indonesian’s Government target of sugar needs or swasembada gula in Indonesia by 2024. PT. MSM gave investment to the East Sumba Regional Government to build sugarcane plantation in the region to support the government’s plan, one of them is in Desa Wanga, Umalulu District. The investment of PT. MSM actually have significant benefits both for regional development plans and the community welfare in East Sumba, yet resistance emerged from the people of Paraingu Patawangu community. This article focuses on the reason why the Paraingu Patawangu people perform resistance against PT. MSM, and the forms of their resistances. The study was conducted using qualitative research methods with ethnographic model for two months. Data collection was carried out by observation techniques, interviews, and library studies. Based on the research, it is known that there are three factors which is causing the resistance and at least four forms of resistances.